The Neotropical Species of the Ant Genus Strumigenys Fr. Smith: Group of Gundlachi (Roger) - William L. Brown (Psyche: A Journal of Entomology)
This paper is a continuation of my series on the New World fauna of the dacetine ant genus Strumigenys Fr. Smith. Earlier parts, containing keys to the abbreviations for measurements and proportions, may be found in Jour. New York Ent. Soc. 61: 53-59, 1o1-11o (1953). In addition to these, other parts have been published or are being prepared. At the end of the series, an illustrated key to the New- World members of the genus will be forthcoming.